Deformation and exhumation of the Higher and Lesser Himalayan Crystalline sequences in the Kumaon region, NW-Himalaya based on structural and fission-track analysis - Patel, RC; Lal, Nand; Kumar, Yogesh (Himalayan Journal of Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/hjs.v5i7.1294 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.101-102